1997
DOI: 10.1037/0022-0167.44.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, connection, and passion: A qualitative study of the career development of highly achieving African American–Black and White women.

Abstract: Strauss & J. Corbin, 1990) was used to generate a theory of the career development of participants that was grounded in their experiences, as related in semistructured, in-depth interviews. The theoretical model generated from the data included 5 major components: (a) a core story consisting of participants' work behaviors and attitudes, which is enacted within (b) sociocultural, (c) personal background, and (d) current contextual conditions and leads to particular career (e) actions and consequences. The emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
143
3
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(168 citation statements)
references
References 27 publications
17
143
3
5
Order By: Relevance
“…The following diagrams in figure 1 [in Appendix] depict various types of love based on amounts and balance of each dimension. Sternberg's (1988) triangular love theory is conceptually consistent with results of recent qualitative research on workplace motivation (Gordon, 2005;Richie, Fassinger, Linn, Johnson, Prosser, and Robinson, 1997). Both Gordon (2005) and Ritchie et al (1997) based their research on working women and found three universal themes that align with Sternberg's (1986) three dimensions of love.…”
Section: Sternberg's Theory Of Interpersonal Lovesupporting
confidence: 64%
See 2 more Smart Citations
“…The following diagrams in figure 1 [in Appendix] depict various types of love based on amounts and balance of each dimension. Sternberg's (1988) triangular love theory is conceptually consistent with results of recent qualitative research on workplace motivation (Gordon, 2005;Richie, Fassinger, Linn, Johnson, Prosser, and Robinson, 1997). Both Gordon (2005) and Ritchie et al (1997) based their research on working women and found three universal themes that align with Sternberg's (1986) three dimensions of love.…”
Section: Sternberg's Theory Of Interpersonal Lovesupporting
confidence: 64%
“…Both Gordon (2005) and Ritchie et al (1997) based their research on working women and found three universal themes that align with Sternberg's (1986) three dimensions of love. Gordon's (2005) process theme, which taps into how a worker is challenged by and engaged in her job's activities, and Richie et al's (1997) passion for the work theme both align with Sternberg's passion dimension. Gordon's (2005) purpose theme, or the extent to which the employee feels compelled to fulfill herself through her work, and Richie et al's (1997) persistence theme both align with Sternberg's commitment dimension.…”
Section: Sternberg's Theory Of Interpersonal Lovementioning
confidence: 99%
See 1 more Smart Citation
“…Also, the study intended to contextualize phenomena and allow for the exploration of the experiences of participants from their own perspectives and words (Richie, Fassinger, Linn, Johnson, Prosser, & Robinson, 1997). From a phenomenological perspective, it was important to realize that there was no objective or separate reality; there was only what the women knew based on their experiences and what these experiences signified to them.…”
Section: Methodsology Theoretical Framework: Hermeneutic Phenomenologymentioning
confidence: 99%
“…Studies on personal factors in career development emphasize gender and gender role socialization (Astin, 1984;Betz & Fitzgerald, 1987;Eag1y, 1987;Gottfredson, 1996); personality (Betz & Fitzgerald;Ritchie, Fassinger, Linn, Johnson, Prosser, & Robinson, 1997;Wentling, 2003;White, 1995); the acquisition and development of human capital such as education, formal skills/abilities, and job tenure (Burke, 2007;Knoppers, 1992); and self-efficacy (Betz, 2004;Lent et aI., 1994). Eccles (1994) posited, "Understanding women's occupational choices requires a broad view of the options and roles available to women" (p. 605).…”
Section: Personal Factors Personal Factors Include a Range Of "Intramentioning
confidence: 99%